A Flame Retardant Ionic Conductor Additive for Safety-Reinforced Liquid Electrolyte of Lithium Batteries. Issue 7 (1st January 2017) - Wang, Qingfu; Liu, Pingping; Li, Shizhen; Wang, Xiao; Li, Fangzhou; Ma, Jun; Chai, Jingchao; Zhang, Jianjun; Xu, Gaojie; Huang, Zhaoge; Cui, Guanglei
Abstract : An ionic conducting ethyl phosphate-polyethylene glycol based copolymer (abbreviated as EPCP) as a promising flame retardant additive is presented in this study. The flammability tests demonstrate that the liquid electrolyte with 15 wt% EPCP (abbreviated as EPCP15-LE) is totally nonflammable. More importantly, benefitted from the ionic transport capability of EPCP, the ionic conductivity of EPCP15-LE at room temperature is comparable with the liquid electrolyte (shorted as LE). Moreover, the resultant electrolyte possessed wide electrochemical window (4.3 V), which can be matched with relatively high voltage cathode materials. In addition, the cell using EPCP15-LE exhibits superior cycle performance and excellent rate capability. In a word, this flame retardant ionic conductor is a promising additive for safety-reinforced lithium battery.